Increasing Consumer Hedonic Shopping Motivation in Encouraging the Purchase of Local Skincare Products 'Somethinc' - Dwiputrianti, Septiana; Nugroho, Adhika Bergi; Islam, Varih Rizky; Kurniawan, Iwan (Universitas Medan Area, 2023)
This study aimed to find out whether hedonic shopping motivation has a potential impact on impulse purchases of local skincare products ''Somethinc''. Hedonic shopping motivation is an action that can encourage certain behaviors, one of which is impulse purchases. However, with social media, of course, a lot of information can be obtained so that consumers become more critical of product purchases and make business actors have to create offers and products that can compete. The method in this study is quantitative descriptive using non-parametric statistics of spearman rank correlation analysis. The sampling technique uses non-probability accompanied by a purposive sampling method through questionnaires. The study population is consumers of the facial care products brand 'Somethinc' in Bandung City. The sample used based on the Lemeshow formula was 390 respondents. The results showed that the increase in hedonic shopping motivation on the TikTok platform had a significant effect on impulse purchases and had a fairly high relationship. Based on the results of the analysis, the actions that 'Somethinc' can apply to trigger impulse purchases are based on hedonic shopping motivation, namely conceptualizing collaboration during live streaming with beauty enthusiasts and creating attractive offers. This can encourage consumers to make purchases while providing an interesting experience for consumers in online shopping activities.